Two-Hour Lactate Clearance Predicts Negative Outcome in Patients with Cardiorespiratory Insufficiency. (15th June 2010) - Scott, Sean; Antonaglia, Vittorio; Guiotto, Giovanna; Paladino, Fiorella; Schiraldi, Fernando
Abstract : Objective . To evaluate 2-hour lactate clearance as a prognostic marker in acute cardiorespiratory insufficiency. Design . Prospective observational study. Setting . Emergency Department (ED) and 16-bed medical High Dependency Unit (HDU). Methods and Main Results . 95 consecutive admissions from the ED for acute cardiorespiratory insufficiency were prospectively enrolled. Arterial lactate concentration was assessed at ED arrival and 1, 2, 6, and 24 hours later. The predictive value of 2-hour lactate clearance was evaluated for negative outcomes defined as hospital mortality or need for endotracheal intubation versus positive outcomes defined as discharge or transfer to a general medical ward. Logistic regression and ROC curves found 2-hour lactate clearance> 15% was a strong predictor of negative outcome (P < .0001 ) with a sensitivity of 86% (95%CI = 67 %–95%) and a specificity of 91% (95%CI = 82 %–96%), Positive predictive value was 80% (95%CI = 61 %–92%), and negative predictive value was 92% (95%CI = 84 %–98%). Conclusions . Systematic monitoring of lactate clearance at 2 hours can be used in to identify patients at high risk of negative outcome and perhaps to tailor more aggressive therapy. Equally important is that a 2-hour lactate clearance> 15% is highly predictive of positive outcome and may reassure clinicians that the therapeutic approach is appropriate.